Awake caudals and epidurals should be used more frequently in neonates and infants. Issue 1 (30th September 2014) - Marhofer, Peter; Keplinger, Maya; Klug, Wolfgang; Metzelder, Martin L.; Morton, Neil
Summary The current literature provides fundamental insights regarding the neurotoxic potency of various general anesthetic drugs in neonates and small infants. Therefore, considerations to minimize the use of general anesthetic drugs in this age group are required. The use of caudal and epidural anesthesia under sedation is one possibility to minimize the use of general anesthetic drugs. A large number of surgical procedures can be managed with this anesthetic concept. Training, practical hand skills, good infrastructure, a well‐defined indication, and a team approach including the entire operation room staff are the major prerequisites to implement these techniques in the daily clinical practice. This review article discusses all present aspects and possible future evolutions of caudal and epidural anesthesia under sedation.